2021
DOI: 10.3390/ijms22020803
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of microRNAs in βCell: Between Phenotype Maintenance and Protection

Abstract: Diabetes mellitus is a group of heterogeneous metabolic disorders characterized by chronic hyperglycaemia mainly due to pancreatic β cell death and/or dysfunction, caused by several types of stress such as glucotoxicity, lipotoxicity and inflammation. Different patho-physiological mechanisms driving β cell response to these stresses are tightly regulated by microRNAs (miRNAs), a class of negative regulators of gene expression, involved in pathogenic mechanisms occurring in diabetes and in its complications. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…To date, approximately 50 miRNAs have been identified in islets, some of which have been reported to be involved in β-cell function and proliferation [83]. In particular, miR-204, -375, -483, -184, -124, -30, -24, and -7 play important roles in the regulation of β-cell identity and function in the pancreas [84][85][86][87][88][89][90][91][92]. For example, miR-204 is the most abundant miRNA in human β-cells and is known to regulate the expression of MafA and GLP-1 receptors [93,94].…”
Section: Micrornas (Mirnas) and Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…To date, approximately 50 miRNAs have been identified in islets, some of which have been reported to be involved in β-cell function and proliferation [83]. In particular, miR-204, -375, -483, -184, -124, -30, -24, and -7 play important roles in the regulation of β-cell identity and function in the pancreas [84][85][86][87][88][89][90][91][92]. For example, miR-204 is the most abundant miRNA in human β-cells and is known to regulate the expression of MafA and GLP-1 receptors [93,94].…”
Section: Micrornas (Mirnas) and Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Indeed, miRNAs are relatively stable and can be easily detected in biological fluids [18]. Several miRNAs are tissue specific and have been associated to numerous pathological conditions, including diabetes mellitus and its complications [17,18,44]. Accordingly, extensive work on circulating miRNAs in T2D has revealed that many miRNAs are differentially expressed between T2D patients and control subjects [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plasma levels of miR-15a-5p correlate with disease severity [52]. Among β-cell-specific miRNAs, miR-375 has also been related to β-cell damage/proliferation and to insulin secretion, and is involved in the maintenance of islet architecture [44,50]. In more detail, miR-375 leads to a reduced glucose-stimulated insulin secretion by inhibiting exocytosis and downregulating insulin expression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have highlighted a pivotal role of miRNAs in the molecular mechanisms contributing to loss of functional β-cell mass, such as β-cell dysfunction (i.e., impaired insulin production and secretion), differentiation, survival and apoptosis, which ultimately lead to T2D [ 166 ] ( Table 2 ).…”
Section: Non-coding Rnas In Metabolic Diseases: State Of Artmentioning
confidence: 99%